Embedded Supervision: How to Build Regulation into Decentralised Finance - Raphael A. Auer (Center for Economic Studies and ifo Institute (CESifo), 2022)
The emergence of so-called "decentralised finance" (DeFi) and a shadow financial system of cryptocurrency exchanges and stablecoin issuers raises the challenge of how to apply technology-neutral regulation so that similar risks are subject to the same rules. This paper makes the case for embedded supervision, ie a regulatory framework that provides for compliance in decentralised markets to be automatically monitored by reading the market's ledger. This reduces the need for firms to actively collect, verify and deliver data. The paper explores the conditions under which distributed ledger data may be used to monitor compliance. To this end, a decentralised market is modelled that replaces today's intermediary-based verification of legal data with blockchain-enabled credibility based on economic consensus. The key results set out the conditions under which the market's economic consensus would be strong enough to guarantee that transactions are economically final, so that supervisors can trust the distributed ledger's data. The paper concludes with a discussion of the legislative and operational requirements that would promote low-cost supervision and a level playing field for small and large firms.
Keywords: D40; D20; E42; E51; F31; G12; G18; G28; G32; G38; K22; K24; L10; L50; M40; 330; decentralised finance; DeFi; tokenisation; asset-backed tokens; stablecoins; crypto-assets; cryptocurrencies; CBDC; regtech; suptech; regulation; supervision; Basel III; proportionality; blockchain; distributed ledger technology; digital currencies; proof